Znaczenie zamków dla rozwoju funkcji turystycznej i edukacyjnej (na przykładzie regionu Mazowsza) - Pawlikowska-Piechotka, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The majority of Mazovia Region castles have function of museum or gallery and it is the function, it seems, welcomed both from the point of view of historic relics protection needs, and the development of sustainable tourism: first of all the sight-sees tourism (as the educational activity) and cultural tourism (concerts, theatre performances, competitions, festivals). Some castles also play role as cultural center of local community in creative way, becoming strong magnet and important attraction. It should be also underlined that in some castles, particularly in those located outside popular touristy routs, still exists a chance to create interesting and important centers influencing on the cultural life of local societies and a chance of implementing some education programs on the subject of tradition and history of given region (with accentuation the local identity). Such proposal of the new forms of cultural life (thanks to the initiative of local authorities as well as the administrator the historic castle), would be simultaneously a chance of promotion the region, a chance of development some sustainable, pro-ecological forms of tourism (sight - seeing tourism and cultural tourism). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 155-164